Genome-wide DNA methylation dynamics at “heading” stage of panicle and flag leaf in contrasting rice cultivars under field drought conditions - Jajo, Ringyao; Kansal, Shivani; Mathur, Saloni; Raghuvanshi, Saurabh (Frontiers in Plant Science, 2025)
IntroductionDrought stress induces widespread genome-wide alterations in DNA methylation of rice. These changes work to alter gene expression and are relatively unexplored in reproductive tissues like flag leaf and panicle under field drought conditions. This study aims to explore the same in the panicle and flag leaf tissue of IR64 (drought-sensitive) and N22 (drought-tolerant) rice cultivars under field-drought conditions during the ‘heading’ stage of development.MethodsFor the same, we generated whole-genome bisulfite sequencing libraries from the corresponding tissues and analysed them in detail.Results and discussionThe DNA methylation dynamics in adult tissue (flowering stage) was found to be clearly distinct from that of the seedling stage. Further, the contrasting rice genotypes also exhibited cultivar-specific and drought-induced dynamism in the methylation signatures. Notably, the two cultivars demonstrate inherent distinctions in sequence preferences of hyper- and hypo-methylation even prior to experiencing drought stress, and these preferences persist under the influence of the stress. Approximately 90% of the drought-induced differentially methylated region (DMR) are cultivar-specific, and about 70% of the cultivar differences (cultivar-DMR) under stress are unique compared to control condition. There is higher prevalence of hyper-methylated DMR that co-localized with differentially expressed genes in panicle. DMR of CHH sequence exhibit stronger negative correlation with expression compared to CpG and CHG sequence. Examination of differentially expressed genes with DMR highlights their functional relevance under drought stress, especially with DMR found in gene bodies and promoter regions. Notably, in panicle, methylation divergence of the two cultivars influences flowering regulation genes. Additionally, the findings also suggest a regulatory role for DNA methylation in drought induced response of miRNA genes, particularly in the panicle of N22 cultivars.